Pulmonary rehabilitation. Issue 3 (March 2014) - Lameris, Madeleine; Atkins, Christopher
The burden of chronic obstructive pulmonary disease (COPD) on the healthcare system is significant, entailing supportive rather than curative management. Pulmonary rehabilitation (PR) not only improves functional exercise capacity, dyspnoea and overall health status, but also provides economic and societal advantages. The National Institute for Health and Care Excellence and the British Thoracic Society both support the provision of PR for nearly all COPD patients who are symptomatic. This article explains the nature of PR, how it benefits patients with COPD, and how GPs need to be involved in promoting PR to their patients and local commissioners.